2021
DOI: 10.3390/joitmc7020150
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Trust Seals in European and Latin American Commercial Transactions

Abstract: The emergence of the Internet as a commercialization method has offered organizations many opportunities. However, when buyers want to execute a transaction online, a certain distrust typically accompanies the need to provide personal data. To address this problem, assurance seals have been designed for use on websites. Different guarantee logos certify compliance with buyer protection laws and offer transparency in the commercial process. Thus, assurance seals displayed on the websites of sellers that adhere … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 73 publications
0
4
0
1
Order By: Relevance
“…According to Lȃzȃroiu et al (2020), who studied 94 students who had just graduated from the Sfax higher business school, attitudes about behavior and social norms influence whether or not students want to start their own business. A study of 250 university students by Jiménez et al (2021) found a similar positive correlation. It was found that students' attitudes toward entrepreneurship have an impact on their entrepreneurial intentions (Campbell, 2019).…”
Section: Conclusion and Policy Recommendationmentioning
confidence: 68%
“…According to Lȃzȃroiu et al (2020), who studied 94 students who had just graduated from the Sfax higher business school, attitudes about behavior and social norms influence whether or not students want to start their own business. A study of 250 university students by Jiménez et al (2021) found a similar positive correlation. It was found that students' attitudes toward entrepreneurship have an impact on their entrepreneurial intentions (Campbell, 2019).…”
Section: Conclusion and Policy Recommendationmentioning
confidence: 68%
“…Companies and organisations that offer ecommerce services must understand their customers' percep-tions and how the companies connect with them. People typically avoid transacting over the Internet due to worries regarding consumer information exploitation, reliability, fraud, and payment [Jiménez et al, 2021]. So, user experience is a result of the features, performance, system interactivity, or products that the user has experienced as a result of previous experiences, abilities, and context of use.…”
Section: User Experience and Human-computer Interface (Hci)mentioning
confidence: 99%
“…Concerns regarding the exploitation of consumer sensitive data, which allows for fraud and monetary value theft, restrict people from conducting internet transactions [Jiménez et al, 2021]. According to Ang and Lee (2000), no purchase choice will be made until the website persuades the buyer that the merchant is reliable.…”
Section: User Experience and Human-computermentioning
confidence: 99%
“…En muchos casos, la existencia de un documento de buenas prácticas relacionado con la sostenibilidad ayuda a mantener la confianza pública porque de alguna manera, dicho documento garantiza que cualquier persona que se suscriba a dicho texto sabrá, en principio, cómo actuar éticamente en este caso en el ámbito de la sostenibilidad. Por tanto, los documentos antes mencionados enumeran ciertos objetivos en el mundo empresarial, como mejorar la reputación corporativa , evitar la regulación Doig y Wilson, 1998;López, Dittmar y Vargas, 2021c), atraer inversiones (García y Valor, 2004), mejorar el clima laboral (Manley, 1991), incrementar la eficiencia de la organización (Mezher, Jamali y Zreik, 2002), en áreas significativas, como el medio ambiente, y prevenir conductas inmorales (Shwartz, 2001).…”
Section: Autorregulación De La Sostenibilidad Como Sugerente Manifestación De Rseunclassified